Anti-inflammatory activity of 4-arylcoumarins from endophytic Streptomyces aureofaciens CMUAc130 in murine macrophage RAW 264.7 cells - Thongchai Taechowisan (2018)
This research was undertaken to test the in vitro anti-inflammatory action of 5,7,4′-trimethoxy-4-phenylcoumarin and 5,7-dimethoxy-4-phenylcoumarin produced by Streptomyces aureofaciens CMUAc130. The effects of the two coumarins were investigated on the formation of NO, PGE2, and TNF-α and also on inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in lipopolysaccharide (LPS)-induced murine macrophage RAW 264.7 cells. The data obtained were consistent with the modulation of iNOS enzyme expression. A similar effect was also observed when LPS-induced PGE2 release and COX-2 expression were tested. The inhibitory effects were shown in concentration-dependent manners. The 5,7,4′-Trimethoxy-4-phenylcoumarin and 5,7-dimethoxy-4-phenylcoumarin also mildly but significantly reduced the formation of TNF-α. Copyright © Informa Healthcare.